دراسة تحليلية لمعدل العائد على الاستثمار في رأس المال البشري في الساحل السوري - دريباتي يسيرة; ابراهيم عمار (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يهدف البحث إلى قياس معدل العائد على الاستثمار في رأس المال البشري في الساحل السوري بتطبيق معادلة الكسب المينسرية وذلك من خلال توزيع استبيان على مجموعة من العاملين في القطاع العام وفي القطاع الخاص المنظم الذين يمارسون عملهم في الساحل السوري, وتحليله باستخدام برنامج Spss وذلك بالاعتماد على طرائق الاستدلال الإحصائي والاختبارات الإحصائية. وتوصل البحث إلى النتائج التالية:المستوى التعليمي والخبرة يفسران 70% من التغير الحاصل في الدخل في القطاع العام و36% من التغير الحاصل في الدخل في القطاع الخاص, يرتبط التدريب بالمستوى التعليمي ارتباطاً ضعيفاً, انخفاض معدل العائد على الاستثمار في رأس المال البشري في الساحل السوري, إن معدل العائد على الاستثمار في رأس المال البشري في القطاع العام لا يختلف عن معدل العائد على الاستثمار في رأس المال البشري في القطاع الخاص في الساحل السوري. The research aims to measure the rate of return on investment in human capital in the Syrian coast applying equation earning Alimsria and through the distribution of a questionnaire to a group of employees in the public sector and the organized private sector who have their work in the Syrian coast, and analyzed using Spss, based on methods statistical inference and statistical tests. The research found the following results: level of education and experience explain 70% of the change in income in the public sector and 36% of the change in income in the private sector, linked to the training level of education is closely weak, low rate of return on investment in human capital in the Syrian Coast the rate of return on investment in human capital in the public sector is no different from the rate of return on investment in human capital in the private sector in the Syrian coast.